1983
DOI: 10.2136/sssaj1983.03615995004700040004x
|View full text |Cite
|
Sign up to set email alerts
|

Furrow and Trickle Irrigation: Effects On Soil Oxygen and Ethylene and Tomato Yield

Abstract: This study was conducted to determine whether low soil oxygen levels or high soil ethylene reduce tomato (Lycopersicon esculentum) yield in clay soil, when high temperatures are combined with trickle or furrow irrigation. Treatments were daily or weekly trickle irrigations (100 or 120% of pan evaporation) and furrow irrigations (5‐ or 10‐d intervals). Soil oxygen and ethylene levels and soil matric potentials were measured at the 20‐ and 40‐cm depths immediately before and during part of the fruiting cycle. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
4

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 0 publications
0
22
0
4
Order By: Relevance
“…Xie et al (2010) showed that oxygenation of the root zone at fixed intervals increased the yield of greenhouse-produced sweet melon. Meek et al (1983) reported higher yields of tomatoes were related to higher oxygen contents in the soil root zone before and during the fruit-enlarging stage.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Xie et al (2010) showed that oxygenation of the root zone at fixed intervals increased the yield of greenhouse-produced sweet melon. Meek et al (1983) reported higher yields of tomatoes were related to higher oxygen contents in the soil root zone before and during the fruit-enlarging stage.…”
Section: Introductionmentioning
confidence: 91%
“…Repeated exposure to periods of low rhizosphere soil aeration would be expected for subsurface trickle irrigation since water is usually applied at a lower amounts and higher frequencies than other forms of irrigation. Meek et al (1983) showed that the rhizosphere soil oxygen content was higher under weekly drip irrigation or furrow irrigation than under daily drip irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Because the tomato is one of the most sensitive species to water and air in the soil (Bradford and Yang, 1981), the present study used greenhouse tomatoes as its study subject. Higher tomato yields are related to higher oxygen contents in the soil root zone (Meek et al, 1983;Niu et al, 2012aNiu et al, , 2012b. Observed changes in plant growth were mainly because of the changes in nutrient cycling and physiological status, and soil-available nutrients were affected by soil microorganisms and soil enzyme activity.…”
mentioning
confidence: 99%
“…Drip (DI), or trickle, irrigation is widely considered in the literature to have advantages over sprinkle (SI) or other types of irrigation (Shmueli and Goldberg 1971;Goldb"rE und ,2U Shmueli l97l; Bernstein and Francois 1973;Meek et al 1983;Bhella 1988;Rubino and Tarantino 1988;Sanders et al 1989 (Bogle et al 1989;Locascio et al 1989;Sanders et al 1989). There are some advantages to SI, such as plant canopy temperature reduction (Tan 1993) and frost protection in the early season (Rogers and Modlibowska 1962).…”
mentioning
confidence: 99%